Makna Kualitas Hidup pada Penyintas Autoimun Kronis yang Bekerja - Maulana, Ahmad Sidiq; Hamzah, Imam Faisal (Universitas Negeri Makassar, 2025)
Chronic autoimmune diseases have a multidimensional impact on the lives of individuals, affecting them physically, psychologically, socially, and spiritually. For those who remain employed, the challenges become increasingly complex as they must balance their health conditions with professional demands. This study aims to explore the meaning of quality of life as experienced by individuals with chronic autoimmune diseases who continue to work. The research adopts a qualitative approach using descriptive phenomenology. Participants consisted of three working individuals living with autoimmune conditions, selected through snowball sampling. Data were collected through semi-structured interviews, observations, and medical document analysis. The findings reveal that quality of life is perceived as a process of self-regulation, adaptation to physical limitations, and ongoing emotional management. Spirituality emerges as a fundamental pillar supporting self-acceptance and nurturing hope amid health uncertainties. Furthermore, participants maintain a sense of purpose through optimism, support from family and workplace institutions, and the redefinition of self-identity. Psychological ambivalencesuch as guilt or emotional burdenis commonly experienced but is managed through spiritual reflection and self-awareness. In conclusion, quality of life for working individuals with autoimmune conditions results from a complex interplay of internal and external factors that mutually reinforce one another. Recommendations are directed toward institutions to implement inclusive and adaptive work policies to ensure the sustained participation and well-being of employees living with chronic illnesses.